2018
DOI: 10.3390/bs8070061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dance Movement Therapy on Adult Patients with Autism Spectrum Disorder: A Randomized Controlled Trial

Abstract: This study examines the effects of dance movement therapy (DMT) on empathy for adults with autism spectrum disorder (ASD). DMT based on the embodiment approach offers body-centered interventions, such as mirroring techniques, to address the needs of ASD patients. Accordingly, findings of a feasibility study suggest that DMT may be an effective approach for clients on the ASD spectrum. The present study is a randomized controlled trial that was conducted as a multicenter study within the framework of the EU-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 49 publications
2
36
0
12
Order By: Relevance
“…In line with Mastrominico et al (2018), Koch, Mehl, Sobanski, Sieber, and Fuchs (2015) conducted a feasibility study with an interest in the specific effects of mirroring in movement on well‐being, body awareness, self‐other distinction, social competence and empathy in young adults with ASD. Participants in the intervention group, which included dyadic movement exercises and verbal processing, showed significant improvements with medium to large effect sizes in body awareness ( d = 0.62), self‐other awareness ( d = 0.72), psychological well‐being ( d = 0.68) and social skills ( d = 0.67).…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…In line with Mastrominico et al (2018), Koch, Mehl, Sobanski, Sieber, and Fuchs (2015) conducted a feasibility study with an interest in the specific effects of mirroring in movement on well‐being, body awareness, self‐other distinction, social competence and empathy in young adults with ASD. Participants in the intervention group, which included dyadic movement exercises and verbal processing, showed significant improvements with medium to large effect sizes in body awareness ( d = 0.62), self‐other awareness ( d = 0.72), psychological well‐being ( d = 0.68) and social skills ( d = 0.67).…”
Section: Resultsmentioning
confidence: 83%
“…Although the results did not reach statistical significance at the conventional 0.05 level, they suggested a positive trend towards increased reduction of symptoms in the group receiving the DMT intervention relative to the control group. Mastrominico et al (2018) conducted another RCT examining the effects of DMT on adult patients with ASD after a 10‐week manualized DMT intervention but observed no significant effects. The measure of interest was empathy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies examining the contribution of DMT with adults diagnosed with ASD have found that their ability to synchronize in open and free movement is limited compared to TD but not completely impaired, and researchers recommend using these tools to develop the social skills of empathic tendency, emotional recognition, and affective engagement (Brezis et al, 2017 ). Studies, respectively, show that the practice of mirroring, synchronization, rhythm, and reciprocity in movement contributes to social involvement, body awareness (DeJesus et al, 2020 ), emotional engagement, rapport, and intersubjective communication (Delafield-Butt et al, 2020 ), emotional empathy (Mastrominico et al, 2018 ), and the expression of emotions (Takahashi et al, 2019 ). Several studies in the field describe the effect of 1-h intervention per 6 weeks on regulation, imitation, and interaction (Mateos-Moreno and Atencia-Doña, 2013 ), for 7 weeks on improvement in psychological well-being, body awareness, self-other awareness, and social skills (Koch et al, 2015 ), for 8 weeks on the ability to form relationships (Edwards, 2015 ), and for 10 weeks on emotional expression (Hildebrandt et al, 2016 ), body image (Koch et al, 2016 ), and cognitive empathy (Koehne et al, 2016b ).…”
Section: Asd and Dmtmentioning
confidence: 99%